MSME Development Strategies in Supporting Community Economic Empowerment - Muh Irshan Sachrir; Dini Kamila Salma; Damas Gianlugi Alrizqi; Nurul Haeriyah Ridwan (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2026)
This study aims to analyze the development strategies of Micro, Small, and Medium Enterprises in supporting community economic empowerment. MSMEs play a strategic role in the economy, particularly in employment generation and income improvement. However, their development still faces various challenges, including limited access to capital, low managerial capacity, and limited utilization of digital technology. This study employs a qualitative approach with a descriptive method, using data collection techniques such as interviews, observations, and documentation. The results show that MSME development strategies, including product quality improvement, business diversification, digital technology utilization, and strengthening of business management, are able to enhance business capacity and competitiveness. These improvements have a positive impact on increasing income, creating job opportunities, and strengthening the local economy. Nevertheless, the implementation of these strategies still encounters several constraints that require external support from the government, financial institutions, and business support organizations. Therefore, a comprehensive and integrated MSME development strategy is essential to promote sustainable community economic empowerment.